Surgical Innovations in Vitreo-Retinal Surgery - Sumant Vinayak Sharma; Raja Narayanan (Delhi Journal of Ophthalmology)
Vitreo-retinal surgery has enabled the treatment of multiple posterior segment pathologies, which till few decades back were considered untreatable. With continuing innovation, modern retinal surgery is becoming more efficient and safer, while simultaneously making forays into newer paradigms. In this review article, we look at recent innovations that are changing the practice patterns among surgeons. Surgical innovations in instrumentation, visualisation and automation are discussed. The introduction of ultrasound energy in vitrectomy, termed as hypersonic vitrectomy, promises freedom from complications of current guillotine-based cutters. In terms of new avenues of visualisation, heads up 3-Dimensional (HUD) viewing systems, intraoperative OCT(i-OCT) and endoscopic vitrectomy permit better ergonomics, real time cross-sectional imaging and visualisation in opaque media respectively. Automation of surgical steps via robotic surgery heralds a new era in surgical safety.